Academic growth expectations for students with emotional and behavior disorders. Issue 8 (3rd July 2017) - Ysseldyke, Jim; Scerra, Carmine; Stickney, Eric; Beckler, Amanda; Dituri, Joan; Ellis, Karen
Abstract: Computer adaptive assessments were used to monitor the academic status and growth of students with emotional behavior disorders (EBD) in reading ( N = 321) and math ( N = 322) in a regional service center serving 56 school districts. A cohort sequential model was used to compare that performance to the status and growth of a national user base of more than 7, 500, 000 students without disabilities. Consistent with numerous previous findings, status or level of performance of students with EBD was consistently low relative to their nondisabled peers. However, for the most part the students with significant EBD demonstrated rates of growth similar to the nationwide sample of nondisabled peers. There was considerable variability in the academic growth of students across grades and between treatment programs, and this variability is described and discussed. Implications for policy and practice in student progress monitoring and teacher evaluation systems are discussed.